Analisis Putusan Hakim Pengadilan Agama Solok Tentang Asal Usul Anak dan Relevansinya dengan Maqashid Syariah - Irvan Refliandi; Mona Eliza (Perwakilan, 2023)
The next generation of nations, which includes children, will alter the course of global civilization. Since blood links are the primary source of family relationships because they serve as the family's "glue" and "bond," it is crucial to discuss how children come into the world. As was the case in the application for determining the origins of children submitted to the Solok Religious Court where a husband and wife became the applicants and requested that their child be recognized as a legitimate child, but in reality, the child was born as the result of extramarital affairs marry the applicant and enter into an unregistered marriage in which one party is still regarded as being legally married to another woman due to the fact that they lack a divorce decree or a private divorce. This study aims to examine the legal criteria utilized by the Solok Religious Court judges to establish the parentage of a child and its applicability to maqashid sharia. This study takes a qualitative approach while using a descriptive-analytical strategy. Based on the study's findings, it can be said that the legal criteria used by judges, such as marriage laws, Constitutional Court rulings, Islamic law, and the Fatwa of the Ulema Council, are relevant to maqasid sharia and are consistent with the idea of ad-Dharuriyyah on maqashid sharia, which is to protect the soul and the lineage.